2015
DOI: 10.1051/fruits/2015044
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and physicochemical characteristics of three pomegranate cultivars (Punica granatumL.) grown in northern Algeria

Abstract: Introduction. In northern Algeria, various pomegranate cultivars (Punica granatum L.) are produced in the region of Mitidja. However, to date, no study has been published on the characteristics of the locally grown cultivars. The objective of the present study was to investigate the morphological and physicochemical characteristics of the fruit of three local pomegranate cultivars. Materials and methods. Our study focused on a comparison of the cultivars 'Doux de Koléa', 'Doux de Messaad' and 'Bordj Mira 11', … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
2
1
0
Order By: Relevance
“…The TA content, which varies between 0.30 (KH1) and 0.53 (HM1) g citric acid/L, is similar to values reported with Spanish varieties such as PTO4 (0.30), Indian cultivars such as Ganesh (0.39), Bhagwa (0.36) and various ones from South Africa, Croatia, Tunisia, Algeria, Greece and China (subtropical monsoon climate) (Drogoudi et al, 2005;Radunić et al, 2011;Chandra et al, 2012;Mir et al, 2012;Hernández et al, 2014;Meziane et al, 2016;Liu et al, 2023). However, previous studies have shown that the TA of some local Moroccan varieties, ranging from 2.14 to 4.71 g/L, is higher than those reported in this study (Legua et al, 2011;Martínez et al, 2012).…”
Section: Ph Titratable Acidity and Total Soluble Solidssupporting
confidence: 81%
See 1 more Smart Citation
“…The TA content, which varies between 0.30 (KH1) and 0.53 (HM1) g citric acid/L, is similar to values reported with Spanish varieties such as PTO4 (0.30), Indian cultivars such as Ganesh (0.39), Bhagwa (0.36) and various ones from South Africa, Croatia, Tunisia, Algeria, Greece and China (subtropical monsoon climate) (Drogoudi et al, 2005;Radunić et al, 2011;Chandra et al, 2012;Mir et al, 2012;Hernández et al, 2014;Meziane et al, 2016;Liu et al, 2023). However, previous studies have shown that the TA of some local Moroccan varieties, ranging from 2.14 to 4.71 g/L, is higher than those reported in this study (Legua et al, 2011;Martínez et al, 2012).…”
Section: Ph Titratable Acidity and Total Soluble Solidssupporting
confidence: 81%
“…As shown in Table 2, The pH value obtained for KH1 and HM1 is higher than some reported for Spanish, South African, Omani, Moroccan, Tunisian, Indian, Turkian, Iranian, Egyptian, Pakistani, Georgian pomegranate cultivars (Tehranifar et al, 2010;Ozlekci et al, 2011;Gadže et al, 2012;Caliskan & Bayazit, 2013;Ismail et al, 2014;Zaouay et al, 2014;Fernandes et al, 2017;Hota & Dahiya, 2017;Boussaa et al, 2018;Hmid et al, 2018;Usman et al, 2018;Díaz-Perez et al, 2019;Sassi et al, 2020;Meena et al, 2021;El Moujahed et al, 2022), while the pH value obtained for SL1 is closer to the values recorded on some Moroccan varieties such as "Jaune Marrakech" (Legua et al, 2011;Martínez et al, 2012), on Algerian cultivar "Doux de Koléa" (Meziane et al, 2016), on some Indian varieties such as Ganesh and Bhagwa (Hota & Dahiya, 2017) and on some pomegranate cultivars grown in Georgia (Díaz-Perez et al, 2019). Alcaraz-Mármol et al (2017) registered a higher pH than the reported values in the range of 6.02 to 6.78 for cultivars grown in Spain such as Mollar de Elche, Mollar de Orihuela and Valenciana de Albatera.…”
Section: Ph Titratable Acidity and Total Soluble Solidssupporting
confidence: 43%
“…As for its width it varied from 0.101cm in the region of Remchi to 0.118cm in the region of Fellaoucene. The weight of the fruit varied from 203.2g in the region of Ghazaouet to 357g in the region of Remchi, which is slightly bigger than the average according to Martinez et al 2006, and bigger than previous similar studies (Zoubida Kaci Meziane et al 2016). Overall, there is a difference in the morphological characteristics between the individuals of the pomegranate at the level of the regions studied.…”
Section: Variations Of Individuals By Regionmentioning
confidence: 53%